Drug dosing consideration in patients with acute and chronic kidney disease - a clinical update from Kidney Disease: Improving Global Outcomes (KDIGO) - Matzke, Gary; Aronoff, George R.; Atkinson, Arthur J.; Bennett, William M.; Decker, Brian S.; Eckardt, Kai-Uwe; Golper, Thomas; Grabe, Darren W.; Kasiske, Bertram; Keller, Frieder; Kielstein, Jan T.; Mehta, Ravindra; et al. (Kidney international, 2011)
Drug dosage adjustment for patients with acute or chronic kidney disease is an accepted standard of practice. The challenge is how to accurately estimate a patient’s kidney function in both acute and chronic kidney disease and determine the influence of renal replacement therapies on drug disposition. Kidney Disease: Improving Global Outcomes (KDIGO) held a conference to investigate these issues and propose recommendations for practitioners, researchers, and those involved in the drug development and regulatory arenas. The conference attendees discussed the major challenges facing drug dosage adjustment for patients with kidney disease. In particular, although glomerular filtration rate is the metric used to guide dose adjustment, kidney disease does affect nonrenal clearances, and this is not adequately considered in most pharmacokinetic studies. There are also inadequate studies in patients receiving all forms of renal replacement therapy and in the pediatric population. The conference generated 37 recommendations for clinical practice, 32 recommendations for future research directions, and 24 recommendations for regulatory agencies (US Food and Drug Administration and European Medicines Agency) to enhance the quality of pharmacokinetic and pharmacodynamic information available to clinicians. The KDIGO Conference highlighted the gaps and focused on crafting paths to the future that will stimulate research and improve the global outcomes of patients with acute and chronic kidney disease.
Elektronische Reproduktion der Druckausgabe
Gesehen am 12.08.2022